ANALISIS AKTIVITAS BELAJAR DAN LEVEL KOGNITIF SISWA PADA MATERI BAKTERI KELAS X - Eka Ayu Lestari; Suyud Abadi; Sulton Nawawi (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
This study aims to determine the learning activities and cognitive levels of students on Bacteria material class X SMA Negeri 1 Muara Sugihan.This type of research is quantitative descriptive. The study population was all students of class X MIPA 1. The study sample was taken using saturated sampling. The sample used was all students of Class X MIPA 1. The instruments used were observation, interviews, questionnaires and documentation. The data of this study were analyzed with a validity test, a reliability test, a difficulty test, a matter of distinguishing test questions and a percentage test. The results of the study of learning activities obtained visual activity (66,3%) active, verbal (62,5%) active, listening (79,1%) active, writing (72,0%) active, emotional (67,0%) active and mentally (60,8%) are quite active. Then the cognitive level results on the level of remembering (87.9%) are very good, understand (76,8%) good, apply (79,4%) good, analyze (60,9%) good enough, evaluate (58,1%) ) is not good, and creating (59,1%) is not good. Conclusions on average learning activities that can be classified in the active category. The highest percentage is active listening activity (79,1%). The lowest percentage is mental activity (60,8%) quite active. Conclusions cognitive level reaches the level of analyzing. The highest percentage is the level of remembering (87,9%) very well. The lowest percentage is evaluating (58,1%) less well.